Potensi Tepung Cangkang Telur dalam Pengembangan Berbagai Inovasi Makanan Berbasis Kalsium Alami - Muhammad Bahrul Ilmi (Jurnal Agritechno, 2025)
The addition of calcium from eggshell powder is known to have a relatively high absorption rate of 45.59%.The method used in this article is a literature article using review  article technique. The articles used in this article were obtained through a search using several search google scholar. The keywords used in the search were tailored to the problem, namely "eggshell powder" or "eggshell flour" and "eggshell calcium fortification" in Indonesian and "eggshell powder" or "eggshell flour" and "eggshell calcium fortification" in English.The magnesium content in eggshell powder, at 233.16 ppm, indicates that in addition to being a source of calcium, this flour also contains other important minerals. Magnesium plays a role in bone metabolism, nerve function, and muscle function. The magnesium (Mg) content in a 20-gram sample is ± 0.02%. This very high calcium content indicates that eggshell flour is a potential natural source of calcium, even very rich compared to many other food ingredients. The value of 1,831.62 ppm or Calcium (Ca) Content in 20 grams of sample = ± 0.18% indicates the effectiveness of the treatment method (boiling and oven) in maintaining or concentrating the mineral content without much loss.